Geothermal model and development area of a fault-controlled geothermal zone along the Fujian coastal area of southeastern China - Haowei Yuan; Tieya Jing; Yulong Yin; Shoucheng Wei; Haonan Gan; Wentao Zhao; Jian Zhang (Natural Gas Industry B, 2024)
China is rich in geothermal resources, especially in Fujian Province, where 207 exposed hot springs have been discovered. The maximum temperature recorded in geothermal wells is above 121 °C in this province, indicating a high geothermal resource potential. However, large-scale breakthroughs in geothermal exploration are hindered by a lack of clear geothermal genetic models. In this study, the genetic model of a fault-controlled medium–low-temperature convection geothermal zone in the Fujian coastal area was determined by considering the tectonic characteristics of the area and the hydrochemical characteristics of the geothermal fluid (recharge, runoff and discharge characteristics, geothermal reservoir temperature, geothermal fluid circulation depth and renewability). The results showed that the exposed hot springs and high-temperature geothermal boreholes were concentrated in the Fu'an–Nanjing and Changle–Zhao'an fault zones. At the intersection or fault-bend of these two fault zones, there was strong stress release and activity, as demonstrated in the exposed parts of the high-temperature geothermal resources. The Changle–Zhao'an fault zone had a greater circulation depth, with an average heat storage temperature of 140 °C, reflecting high geothermal resource potential. Considering the current temperature of the hot springs, Xiamen Bay and Nanjing–Jiulong River were identified as the next geothermal development zones.